2012
DOI: 10.1603/me11214
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory-InfectedEhrlichia chaffeensisFemale AdultAmblyomma americanumSalivary Glands Reveal Differential Gene Expression

Abstract: Ticks are efficient ectoparasites that are able to steal blood, a rich source of nutrients, from their vertebrate hosts. The nymphal developmental stage of ticks plays an important role for pathogen transmission to human and other animal hosts. In this article, we describe a bloodmeal-based sex differentiation tool to generate adult female ticks infected with Ehrlichia chaffeensis to investigate vector-pathogen interactions (functional genomics and gene expression studies). We demonstrate that there is a corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…Goddard (2003) also successfully inoculated A. americanum ticks with a bacterial pathogen, Rickettsia parkeri , but were unable to produce infections in guinea pigs from those ticks. Karim et al (2012) demonstrated that nymphal lone star ticks could be inoculated with culture-grown E. chaffeensis and the infection in ticks was greater than 80% when assessed after molting to the adult stage, although the authors did not describe its validity for the pathogen transmission. Recently, we validated this study in generating E. chaffeensis infected ticks by a needle inoculation method (Cheng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Goddard (2003) also successfully inoculated A. americanum ticks with a bacterial pathogen, Rickettsia parkeri , but were unable to produce infections in guinea pigs from those ticks. Karim et al (2012) demonstrated that nymphal lone star ticks could be inoculated with culture-grown E. chaffeensis and the infection in ticks was greater than 80% when assessed after molting to the adult stage, although the authors did not describe its validity for the pathogen transmission. Recently, we validated this study in generating E. chaffeensis infected ticks by a needle inoculation method (Cheng et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Before infestation on the host, all unfed ticks were kept at Ϸ28ЊC, with 90% relative humidity (RH), for a photoperiod of 14:10 (L:D) h. Ticks were infested on host and 20 Ð25 ticks were pulled off the host at each time point, 0, 12, 18, 24, 36, 48, 72, 96, 120, 144, 168, and 192 h. Within 4 h of being removed from the sheep, tick tissues were collected from the ticks in ice-cold 100 mM 3-(N-Morpholino)-propanesulfonic acid (MOPS) buffer containing 20 mM ethylene glycol bis-(b-aminoethyl ether)-N, N, NЈ, NЈ-tetraacetic acid (EGTA), pH 6.8. Once dissected, salivary glands and midguts were gently washed in the same ice-cold buffer (Karim et al 2012). Dissected tissues from each time point were pooled together and stored in RNAlater (Ambion, Austin, TX) before extracting total RNA or directly stored in lysis buffer and stored at Ϫ80ЊC.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was puriÞed from pooled salivary glands and midguts from unfed and blood adult female A. maculatum using illustra RNAspin Mini RNA isolation kit (GE Healthcare, Amersham Place, Buckinghamshire, United Kingdom), according to the manufacturerÕs instruction using a slight modiÞcation for tick RNA extractions (Karim et al 2011(Karim et al , 2012. Brießy, the total RNA was eluted into nuclease free water and the concentration of total RNA was determined using the Nanodrop spectrophotometer and stored at Ϫ80ЊC (Karim et al 2011(Karim et al , 2012. The total RNA was reverse transcribed using Moloney Murine Leukemia Virus (MMLV) reverse transcriptase according to manufacturerÕs protocol (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations